32+4m=-3(-5m-2)+2m

Simple and best practice solution for 32+4m=-3(-5m-2)+2m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 32+4m=-3(-5m-2)+2m equation:


Simplifying
32 + 4m = -3(-5m + -2) + 2m

Reorder the terms:
32 + 4m = -3(-2 + -5m) + 2m
32 + 4m = (-2 * -3 + -5m * -3) + 2m
32 + 4m = (6 + 15m) + 2m

Combine like terms: 15m + 2m = 17m
32 + 4m = 6 + 17m

Solving
32 + 4m = 6 + 17m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-17m' to each side of the equation.
32 + 4m + -17m = 6 + 17m + -17m

Combine like terms: 4m + -17m = -13m
32 + -13m = 6 + 17m + -17m

Combine like terms: 17m + -17m = 0
32 + -13m = 6 + 0
32 + -13m = 6

Add '-32' to each side of the equation.
32 + -32 + -13m = 6 + -32

Combine like terms: 32 + -32 = 0
0 + -13m = 6 + -32
-13m = 6 + -32

Combine like terms: 6 + -32 = -26
-13m = -26

Divide each side by '-13'.
m = 2

Simplifying
m = 2

See similar equations:

| -3(n-5)=15+4n | | 6x-2=3x-10 | | 4(1/4+x)=5 | | 7z-4=7z-z | | 6(1+7n)=40+8n | | 2x^2+9x=35 | | -4x^2(5x^2-21x-y)= | | 3(x-1)=-7(x-1) | | 1-5m=6(1-m) | | 7(3x+2)+22=36 | | -0.04x+1.32=1.08 | | 4(6x+5)=2+6x | | -3(4-y)=27 | | -1(3w-4)+12w=3w+4 | | 3m-5=5m+2 | | -27-3k=-6(k+2) | | X+20=6x+5 | | 6-3(2k-4)=-18 | | -3(4-y)=-2 | | r-3.8=9.4 | | -6a+2a=-36 | | 71-17=4a+1 | | 7a-3(a+1)=6-5a | | 1.8+9=-5.7-6 | | 5(3e+5)-25e= | | t^2+9t=18 | | v+31=-3(1-6v) | | 13*4x+2x=1x*6-12 | | 9x*9x+5=41 | | -33+4k=-2(k-4)-5 | | 13*4x+2x= | | 6x^2-5x-1=3 |

Equations solver categories